Penyuluhan Fisioterapi Tentang Osteoarthritis pada Kader dan Komunitas Lansia di Posyandu Dewi Utari V Desa Banjararum RW14 Singosari Kota Malang - Refilda, Erfil; Hasta Baruna, Arys; Vidya Amelia, Ratna (UNIVERSITAS SERAMBI MEKKAH, 2025)
Elderly people usually experience physiological changes in the form of visual and hearing problems, getting tired easily, falling easily, slowing down their movements and gradually becoming less agile. Often one of the problems experienced by the elderly is knee pain (Osteoarthritis). This counseling was held with the aim of providing an explanation to the elderly about knee osteoarthritis and also providing an understanding, especially about the causes of knee osteoarthritis and how to do independent exercise at home correctly with the aim of reducing the complaints complained by an elderly person. The method used is providing counseling in the form of health promotion about osteoarthritis or knee pain to the elderly using leaflets as an outreach medium, giving pre-tests and post-tests in the form of questions to the elderly in order to measure how far elderly posyandu visitors know and the effectiveness of the counseling given and providing education. practice independently at home.